ANALISIS PERTUMBUHAN, ASIMILASI BERSIH DAN PRODUKSI TERUNG (Solanum melongena L.): DOSIS PUPUK KANDANG KAMBING DAN PUPUK NPK - Tengku Boumedine Hamid Zulkifli; Koko Tampubolon; Ahmad Nadhira; Yunida Berliana; Erfan Wahyudi; Razali Razali; Musril Musril (Jurnal Agrotek Tropika, 2020)
Growth, Net Assimilation and Yield Analysis of Eggplant(Solanum melongena L.): Dosage of Goat Manure and NPK FertilizerThe research was aimed to obtain the dose of goat manure, NPK fertilizer and the interaction in increasing the growth and yield of eggplant. The research was usedthe randomized block design factorial with the first factor (goat manure) such as K0= 0 ton.ha-1, K1= 10 ton.ha-1, K2= 20 ton.ha-1 and the second factor (NPK Mutiara 16-16-16) such as P0= 0 ton.ha-1, P1= 100 ton.ha-1, P2= 200 ton.ha-1, P3= 300 ton.ha-1 with three replications. This research was conducted at Jl. Eka Rasmi, Medan Johor Subdistrict, Medan, North Sumatra from August until October 2019. The parameters such as plant height, leaf area, fresh weight of root and shoot, dry weight of root and shoot, total dry weight, fruitweight.plant-1, fruit weight.plot-1, crop growth rate (CGR), relative growth rate (RGR), and net assimilation rate (NAR) wereanalyzed using the ANOVA and the means were followed by DMRT test at the level of 5% used the IBM SPSS Statistics v.20. The results showed an increase in leaf area, fresh weight of shoot, dry weight of root, dry weight of shoot, total dry weight, and fruit weight.plant-1, of eggplant plant with the increasing dose of goat manure up to 20 ton.ha-1of 23.27%; 35.85%; 17.64%; 16.55%; 16.66%; and 17.18%, respectively compared to untreated except plant height. Growth in leaf area, fresh weight of shoot, dry weight of root, dry weight of shoot, total dry weight, fruit weight.plant-1 and fruit weight.plot-1of eggplant plant were increased with increasing NPK fertilizer dosage up to 300 kg.ha-1of 16.88%; 25.96%; 24.08%; 38.37%; 34.46%; 21.85%; and 19.22%, respectively compared to untreated. The interaction of goat manure with NPK does not significantly affect on the growth and yield of eggplant plant. The CGR, RGR, and NARvalue in the giving of goat manure from 10 until 30 days after planting was higher compared to the application of Mutiara NPK fertilizer.